Perspektif Orang Tua Siswa terhadap Program Makan Siang Gratis SD Negeri 101 Maluku Tengah - La Ode Nasir (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
The free lunch program at SD Negeri 101 Central Maluku has drawn significant attention, particularly from parents who are the primary stakeholders of this initiative. Based on in-depth interviews with 20 parents from various economic and social backgrounds, it was found that the majority of respondents responded positively to the implementation of the program. They considered it highly beneficial in reducing daily household expenses, especially for their children's meals during school hours. Approximately 85% of parents stated that since the launch of the free lunch program, they no longer needed to provide their children with pocket money or meals from home. This not only reduces daily expenses but also provides peace of mind, knowing that their children are receiving adequate nutrition at school. These findings align with Fitriyani (2022), who stated that school meal programs directly contribute to family economic savings. On the other hand, a small portion of respondents (around 15%) expressed concerns about the quality and hygiene of the food provided. They emphasized the importance of supervision in the preparation and distribution process, ensuring that the program meets not only quantity standards but also nutritional quality and cleanliness. This concern is crucial as it directly relates to students' health. Overall, this study indicates that parents’ perceptions of the free lunch program at SD Negeri 101 Central Maluku are generally positive, with critical notes on food quality, parental involvement, and funding sustainability. These findings offer strong recommendations for policymakers to strengthen this program as part of efforts to improve the quality of basic education in the region.